2022
DOI: 10.3389/fped.2022.812644
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Resistance to Intravenous Immunoglobulin Treatment and Coronary Artery Abnormalities in a Chinese Pediatric Population With Kawasaki Disease: A Retrospective Cohort Study

Abstract: BackgroundThe factors predicting high-risk Kawasaki disease (KD) remain unclear. Therefore, we aimed to determine the risk factors for resistance to intravenous immunoglobulin (IVIG) treatment and coronary artery aneurysm (CAA) development in a Chinese pediatric population with high-risk KD.MethodsWe compared the performances of 11 scoring systems that have been reported to predict IVIG resistance among patients with KD hospitalized from January 2013 through August 2021. Patients were risk-stratified based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
(39 reference statements)
2
11
0
Order By: Relevance
“…In our previous work, we found that the B/A ratio was highly associated with IVIG resistance in high-risk patients, with a Xie Liping risk score of ≥5 points; the same results were observed in high-risk patients with KD as defined by a Kobayashi score of ≥4 points [33]. Based on the findings of previous studies [34][35][36], hepatic dysfunction is a common complication during acute KD episodes and is characterized by elevated serum liver enzymes, hypoalbuminemia, and hyperbilirubinemia.…”
Section: Discussionsupporting
confidence: 66%
“…In our previous work, we found that the B/A ratio was highly associated with IVIG resistance in high-risk patients, with a Xie Liping risk score of ≥5 points; the same results were observed in high-risk patients with KD as defined by a Kobayashi score of ≥4 points [33]. Based on the findings of previous studies [34][35][36], hepatic dysfunction is a common complication during acute KD episodes and is characterized by elevated serum liver enzymes, hypoalbuminemia, and hyperbilirubinemia.…”
Section: Discussionsupporting
confidence: 66%
“…A total of six studies [ 15 , 19 21 , 27 , 28 ] with 1916 KD patients, of whom 180 developed coronary artery aneurysm, were included in this meta-analysis. The heterogeneity tests showed the extinction of significant heterogeneity ( I 2 = 99.3%; P < 0.001), so the random-effect model was used.…”
Section: Resultsmentioning
confidence: 99%
“…All the selected studies were published from 2015 to 2021. Of 17 articles, seven came from China [21,22,24,[26][27][28][29], four from Korea [16,19,20,25], three from Turkey [13,17,18], one from Japan [23], one from Taiwan [14], and one from Thailand [15]. Sixteen studies were retrospective [13][14][15][16][17][18][19][20][21][22][23][25][26][27][28][29], and one study was prospective [24].…”
Section: Characteristics Of Includedmentioning
confidence: 99%
See 2 more Smart Citations